2022
DOI: 10.3389/fphys.2022.824210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia–Hyperoxia Preconditioning on Indicators of Muscle Damage After Acute Resistance Exercise in Male Athletes

Abstract: PurposeThe purpose of this study was to investigate the effects of acute repeated hypoxia–hyperoxia preconditioning on resistance exercise (RE)-induced muscle damage in male athletes.MethodsEleven young male athletes participated in this randomized double-blind counter-balanced crossover study, and were divided into Normoxia (N) and Hypoxia–Hyperoxia (HH) trials. Subjects of the respective trials were supplied with normoxic (FiO2 = 0.21), or alternating hypoxic/hyperoxic air (FiO2 = 0.10/0.99, 5 min each) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…After the first attempt, subjects from both groups switched and performed the same procedure. The study found that muscle injuries and pain after exercise can be alleviated with pre-exercise hypoxia–hyperoxia therapy, but no improvement was found in terms of muscle strength recovery in male swimmers [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first attempt, subjects from both groups switched and performed the same procedure. The study found that muscle injuries and pain after exercise can be alleviated with pre-exercise hypoxia–hyperoxia therapy, but no improvement was found in terms of muscle strength recovery in male swimmers [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“… The articles, the authors, year of publication and the pathologies studied [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 ]. …”
Section: Figurementioning
confidence: 99%
“…Only myoglobin released from damaged muscle cells, both of the heart and of skeletal muscles, enters the bloodstream and sometimes also the urine. The study showed that high-intensity exercise increased the level of myoglobin in healthy people [31]. On the basis of model simulations, the contribution of myoglobin oxygenation to total heme oxygenation can be signi cantly different under pathophysiological conditions, such as diabetes and peripheral arterial disorder [32].…”
Section: Muscle Damagementioning
confidence: 98%